Model Manajemen Fundrising Wakaf di Surabaya (Studi di Yayasan Dana Sosial Al-Falah, Perbandingan Wakaf Selangor, BWI dan Wakaf Global) - Lailiyah Qotrunnada; Muchammad Saifuddin (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2020)
This study is motivated by the low understanding of the community towards waqf and the large potential of waqf. The purpose of this study was to analyze the development of the fundraising strategy carried out by four waqf management institutions. Namely the Surabaya Al-Falah Social Fund Foundation, the Comparison of the Selangor Waqf (PWS), the Indonesian Waqf Board and the Global Waqf. The research method used is through a descriptive qualitative approach with library research data collection techniques. The results showed that the waqf strategy implemented by the four institutions had progressed from the model that YDSF did to raise funds with the Research Funding method which promotes the creation of business results through the development of waqf assets. PWS and BWI are using the same method, namely picking up the ball and waiting for the ball by working together through the Islamic Financial Institution. And the fundamental strategy that can help waqf institutions in the development of information technology is carried out by the Global Waqf Institution, which applies online waqf with an online waqf strategy through the website, transferring accounts and not setting targets. So that the management of waqf can be said to be effective with the existence of several strategies that are best for the success of the institution to achieve its goals.